If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + 5) = 7x + 1 Reorder the terms: -3(5 + 2x) = 7x + 1 (5 * -3 + 2x * -3) = 7x + 1 (-15 + -6x) = 7x + 1 Reorder the terms: -15 + -6x = 1 + 7x Solving -15 + -6x = 1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -15 + -6x + -7x = 1 + 7x + -7x Combine like terms: -6x + -7x = -13x -15 + -13x = 1 + 7x + -7x Combine like terms: 7x + -7x = 0 -15 + -13x = 1 + 0 -15 + -13x = 1 Add '15' to each side of the equation. -15 + 15 + -13x = 1 + 15 Combine like terms: -15 + 15 = 0 0 + -13x = 1 + 15 -13x = 1 + 15 Combine like terms: 1 + 15 = 16 -13x = 16 Divide each side by '-13'. x = -1.230769231 Simplifying x = -1.230769231
| 7(x-7)+2=9-(x+6) | | 3(x-3)=2-8x | | x-3=.75(2-x)+6 | | 2h-3h=15 | | X/0.4=11.25 | | 11x^2=44x | | 5x/x=(8x^3)/x^2 | | Y-4=-8.4 | | lnx^2+3x-1=0 | | -(-2n-5)=-13-n | | 2(3*-4)=22 | | x11/20*30 | | x=11/30x230 | | 4k-5=6k+1 | | 5(m-4)=2m+3 | | -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 |